The Effect Of SMMA And Brand Image On Price Premium In Building Material Supermarket - Johan Pahing Heru Waskito; Hwihanus Hwihanus (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2023)
Social Media Marketing Activity (SMMA) have become one of the popular marketing methods recently. This study aims to evaluate and analyze SMMA in a Surabaya-based building materials supermarket in relation to consumers' willingness to pay a premium price. The population of this research includes all individuals residing in Surabaya who have previously accessed or opened official social media accounts of the building materials supermarket. The sample analyzed consists of 108 respondents aged 17 years and above, who have had social media accounts for at least 6 months. This study collected data using an electronic survey platform. The data were analyzed using Structural Equation Modeling (SEM) aided by SmartPLS for hypothesis testing calculations. The research findings indicate that SMMA significantly influences brand image and premium pricing. However, brand image does not mediate the relationship between SMMA and premium pricing.